Electron-nuclear double resonance spectroscopy (and electron spin-echo envelope modulation spectroscopy) in bioinorganic chemistry - Hoffman, Brian M. (The National Academy of Sciences, 2003)
This perspective discusses the ways that advanced paramagnetic resonance techniques, namely electron-nuclear double resonance (ENDOR) and electron spin-echo envelope modulation (ESEEM) spectroscopies, can help us understand how metal ions function in biological systems.